The effects of three formats of assessment on the achievement of students with hearing disability - Mohd Yasin, Mohd Hanafi; Toran, Hasnah; Md Zamin, Ainul Azmin; Tahir, Lokman (UPM Press, 2012)
The purpose of this paper is to present findings of a factorial-experimental study which investigated the effects of the additional time and examination format in minimizing the language gap faced by hearing impaired students when answering Malay Language question paper in the Primary School Assessment (UPSR). Three formats were tested in this study, namely, Ordinary Format, DEAS I Format and DEAS II Format. Thirty-six hearing impaired students who were in Form One from Seremban, Melaka and Muar were separated into three experimental groups with equal level of Malaysian Language. All the groups answered the comprehension and essay question in the Malaysian Language examination in the actual time and additional time simultaneously. Questionnaires (to teacher and students), interviews, and observation were also conducted. Results showed that for all the three formats, the subjects performed better in extra time than regular time. A comparison of the performance based on the formats revealed higher achievement in the comprehension and writing sections set in regular time and extra time for the subjects exposed to the DEAS II Format. Therefore, extra time and DEAS II Format are successful in minimizing the language gap between hearing impaired students and normal students in the examination. In more specific, the adaptive approach used in DEAS II Format enables a fair assessment of hearing impaired students’ capabilities. Meanwhile, the findings from the questionnaires and interviews showed that both the teachers and students agreed that extra time and appropriate examination format could improve the achievements of hearing impaired students during the examination.